Characterization of Genetic Risk of End-Stage Knee Osteoarthritis Treated with Total Knee Arthroplasty: A Genome-Wide Association Study. (19th October 2022) - Kulm, Scott; Kolin, David A.; Langhans, Mark T.; Kaidi, Austin C.; Elemento, Olivier; Bostrom, Mathias P.; Shen, Tony S.
Abstract : Background: End-stage knee osteoarthritis (OA) is a highly debilitating disease for which total knee arthroplasty (TKA) serves as an effective treatment option. Although a genetic component to OA in general has been described, evaluation of the genetic contribution to end-stage OA of the knee is limited. To this end, we present a genome-wide association study involving patients undergoing TKA for primary knee OA to characterize the genetic features of severe disease on a population level. Methods: Individuals with the diagnosis of knee OA who underwent primary TKA were identified in the U.K. Biobank using administrative codes. The U.K. Biobank is a data repository containing prospectively collected clinical and genomic data for >500, 000 patients. A genome-wide association analysis was performed using the REGENIE software package. Logistic regression was also used to compare the total genetic risk between subgroups stratified by age and body mass index (BMI). Results: A total of 16, 032 patients with end-stage knee OA who underwent primary TKA were identified. Seven genetic loci were found to be significantly associated with end-stage knee OA. The odds ratio (OR) for developing end-stage knee OA attributable to genetics was 1.12 (95% confidence interval [CI], 1.10 to 1.14), which was lower than the OR associated with BMI (OR = 1.81; 95% CI, 1.78 to 1.83) and age (OR = 2.38; 95% CI, 2.32 to 2.45). The magnitude of the OR for developing end-stage knee OA attributable to genetics was greater in patients <60 years old than in patients ≥60 years old (p = 0.002). Conclusions: This population-level genome-wide association study of end-stage knee OA treated with primary TKA was notable for identifying multiple significant genetic variants. These loci involve genes responsible for cartilage development, cartilage homeostasis, cell signaling, and metabolism. Age and BMI appear to have a greater impact on the risk of developing end-stage disease compared with genetic factors. The genetic contribution to the development of severe disease is greater in younger patients. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.